Perceptions of learning as a function of seminar group factors. - Jaarsma ADC; de Grave WS; Muijtjens AMM; Scherpbier AJJ; van Beukelen P (Medical Education, 2008)
CONTEXT Small-group learning is advocated for enhancing higher-order thinking and the development of skills and attitudes. Teacher performance, group interaction and the quality of assignments have been shown to affect small-group learning in hybrid and problem-based curricula. OBJECTIVES This study aimed to examine the perceptions of student groups as to how teacher performance, group interaction and the quality of assignments are related to one another and to learning effects in seminars of 15-30 students in a hybrid curriculum. METHODS We constructed a 28-item questionnaire nd administered it to 639 students attending 32 seminars in Years 1-4 of an undergraduate veterinary curriculum. We performed factor analysis and reliability analysis of the questionnaire. We used correlation and regression analyses to explore the interactions of the four-factor model, with teacher performance, group interaction and quality of assignments as independent variables and the perceived learning effect of the seminars as the dependent variable. RESULTS The response rate was 99%. Teacher performance (b = 0.78) and group interaction () 0.28) significantly influenced the perceived learning effect. The total effect of the quality of assignments (through effects on teacher performance and group interaction) was 0.47. DISCUSSION The strong relationship between teacher performance and learning effect suggests that students rely strongly on their teachers. The negative effect of group interaction may reflect poor alignment of teaching and assessment and poor organisation of group processes. This should be further examined. Comparative studies on seminars are also recommended.